2021
DOI: 10.1038/s41598-021-89462-3
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance of selected halophytes at the two initial growth stages for future management options

Abstract: Scarcity of water and the small area of the agricultural land are considered as the crucial environmental issues challenged the Arabian Gulf countries. In this study, experiments were conducted to identify the salt tolerance during the germination and the seedling stages of some native halophytes in the State of Qatar. Seeds of eight native species (Salsola setifera, Halopeplis perfoliata, Caroxylon imbricatum, Suaeda aegyptiaca, Acacia tortilis, Limonium axillare, Tetraena qatarensis and Aeluropus lagopoides)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Hayne subsp. Tortilis for example, was present in a highly saline location but is not considered a halophyte according to others' research studies [9,10]. Conversely, the species belonging to the genus Salsola are considered halophytes [11], but none of Salsola longifolia and S. gymnomaschala were encountered in a saline area.…”
Section: Resultsmentioning
confidence: 97%
“…Hayne subsp. Tortilis for example, was present in a highly saline location but is not considered a halophyte according to others' research studies [9,10]. Conversely, the species belonging to the genus Salsola are considered halophytes [11], but none of Salsola longifolia and S. gymnomaschala were encountered in a saline area.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, halophytes reduce the cytoplasmic NaCl concentration by discharging them out of the leaf ( Yuan et al., 2016 ). According to the method of classifying halophytes by Breckle (1986) , L. tetragonum is classified as a recretohalophyte with a salt bladder and salt glands on the underside of leaves ( Alhaddad et al., 2021 ). The dicotyledonous halophytes have no significant change in biomass production even at 200 mM of NaCl and have the genetic potential to resist various environmental stresses ( O’Leary et al., 1985 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with those of other authors [21] who showed that glycophytes are not able to accumulate high levels of NaCl in the leaves without damage, unlike halophytes which can maintain a balance osmotic with external salt solutions. At concentrations of 600 mM, for example, seeds of some halophytes germinate and plants grow without significant problems [22] . However, it should be noted that in glycophytes as well as in halophytes, all metabolic processes are affected by salt [23] .…”
Section: Discussionmentioning
confidence: 99%